Problems of recognition and protection of copyright when using works created by means of artificial intelligence - Eresko, Polina Vladimirovna (Известия Саратовского университета. Новая серия: Серия «Экономика. Управление. Право»)
Introduction. Advanced artificial intelligence technology (hereinafter referred to as AI) is being actively introduced around the world, which also poses legal problems for the copyright institution. An urgent task of copyright law is the need to develop positions on the recognition of copyright in works created with the help of AI, and their protection for further use. Theoretical analysis. In the international and Russian law, there are problems in determining the legal status of AI as an object, subject, or quasi-subject of law. According to the Decree of the President of the Russian Federation “On the development of artificial intelligence in the Russian Federation” and the first law on the regulation of AI in world practice, approved by the European Parliament, AI is a complex or system of technological solutions. Thus, at the present stage of the development of AI, it is recognized as an object of law. Еmpirical analysis. It has been revealed that problems of recognition and protection of copyright are associated with determining authorship of works created with the help of AI. The approaches to determining authorship are highlighted, taking into account the role of a person in the process of creating works: they can be a user, a developer or owner of an AI system, or the author of a precedent work on which artificial intelligence was trained. The paper considers the cases when part of a work created by AI goes into the public domain. The determining factor of authorship is the idea and creative concept of a person, implemented with the help of AI systems, according to which the author is a person, and AI is just a tool for creating the results of human intellectual activity.